Pelatihan Business Model Canvas untuk Meningkatkan Minat Kewirausahaan bagi Mahasiswa Fakultas Teknik Universitas Negeri Yogyakarta - Siti Nursipa Wulida; Arya Yusuf (Jurnal Pengabdian KOLABORATIF, 2024)
College graduates must have a strong entrepreneurial spirit to create job opportunities and reduce unemployment rates. Through entrepreneurship education implemented in almost all majors, students can change their mindset to be more innovative in seeking opportunities. However, in reality, there are still shortcomings in the basic business training provided. In line with the above description, engineering students have great potential in the entrepreneurial world due to the ongoing focus on technology and development. Still, their weakness is that engineering students do not fully understand business fundamentals. Therefore, appropriate training is needed to create a business plan framework. The service method used is lectures and question-and-answer sessions. This training has enabled students to understand entrepreneurship, develop an entrepreneurial mindset, participate in business competencies to hone creative ideas and be able to create job opportunities after graduation.